2016
DOI: 10.2319/030316-188.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical treatment of skeletal anterior open bite in adult patients: Posterior build-ups

Abstract: Objective: To (1) evaluate the efficacy of build-ups in the correction of anterior open bite in adults, (2) evaluate their efficacy in producing molar intrusion, (3) analyze skeletal and dental changes, and (4) assess the long-term stability. Materials and Methods: The sample consisted of 93 lateral cephalograms from 31 patients with skeletal and dental anterior open bite. The patients had received orthodontic treatment consisting of bonded resin blocks on the maxillary molars combined with Tip-Edge Plus brack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 15 publications
0
35
0
3
Order By: Relevance
“…The second treatment option was intrusion of the posterior teeth to correct the anterior open bite. Therefore, molar intrusion considered to be the best treatment choice because it leads to an autorotation of the mandible in the counterclockwise direction, thus improving the long anterior facial height (11,12) . However, intrusion of posterior or anterior dentition is always difficult to achieve without the side effect of extrusion of the anchorage teeth (12)(13)(14)(15)(16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second treatment option was intrusion of the posterior teeth to correct the anterior open bite. Therefore, molar intrusion considered to be the best treatment choice because it leads to an autorotation of the mandible in the counterclockwise direction, thus improving the long anterior facial height (11,12) . However, intrusion of posterior or anterior dentition is always difficult to achieve without the side effect of extrusion of the anchorage teeth (12)(13)(14)(15)(16) .…”
Section: Discussionmentioning
confidence: 99%
“…If it is possible to orthodontically intrude posterior teeth, the accompanying changes in occlusal plane, mandibular plane, lower anterior face height, and anterior dental overbite would close the patient's open bite. However, intrusion of posterior or anterior dentition is always difficult to achieve without the side effect of extrusion of the anchorage teeth (10)(11)(12)(13)(14)(15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%
“…In the present systematic review, eight studies used the non-extraction method to correct AOB (8,(12)(13)(14)(15)(16)18,19), five studies used extraction and non-extraction patients (7,9,10,17,24), and one study used only extraction cases (20). Out of five studies that compared extraction and non-extraction methods to treat open-bite malocclusion, four studies (7,9,17,24) did not find any statistically significant difference between extraction and non-extraction methods in long-term stability of treated open-bite, whereas the study by Janson et al (10) showed that the subjects with extraction presented with a high level of stability (74.2%) compared to non-extraction cases (61.9%).…”
Section: Stability Of Corrected Aob With or Without Extractionmentioning
confidence: 99%
“…They include severity of AOB malocclusion prior to treatment, extractions of premolars, correction of open-bite with or without orthognathic surgery, or different methods of retention (4,5). Recently, many studies have been conducted to check the long-term stability of corrected AOB malocclusion (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). When we searched the literature, we came across two systematic reviews of case series studies conducted to assess the effectiveness of orthodontic and orthopedic treatment in AOB correction (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The anterior open bite is one of the most challenging cases to treat in adult patients. 4 Several surgical and non-surgical treatment approaches have been used to manage these cases. Surgical treatment approach involves maxillary impaction allowing forward and upward rotation of the mandible which decrease the lower anterior facial height and correct anterior open bite.…”
Section: Introductionmentioning
confidence: 99%